Adenomyosis, Infertility and Maternal–Fetal Outcomes: Diagnostic and Therapeutic Strategies Across Disease Phenotype—A Narrative Review - Francesco Giuseppe Martire; Eugenia Costantini; Ilaria Ianes; Claudia d’Abate; Giuseppe Sorrenti; Maria De Bonis; Lucia Lazzeri; Errico Zupi (Journal of Clinical Medicine, 2026)
Adenomyosis is a chronic estrogen-dependent disorder that may adversely affect reproductive health. Increasing evidence suggests that its reproductive and obstetric consequences may vary according to disease phenotype, including focal versus diffuse forms and inner versus outer myometrial localization. This narrative review summarizes current evidence on adenomyosis, infertility, recurrent pregnancy loss, and maternal–fetal outcomes, with particular attention to phenotype-specific clinical implications. MEDLINE and Scopus were searched for English-language studies from database inception through March 2026, and the selected evidence was qualitatively synthesized according to the main clinical topics. Available evidence indicates that adenomyosis is associated with impaired fertility through defective endometrial receptivity, progesterone resistance, abnormal uterine peristalsis, chronic inflammation, and immune dysregulation. Adenomyosis has also been associated with miscarriage and adverse obstetric outcomes, including preterm birth, hypertensive disorders, placental dysfunction, fetal growth restriction, and postpartum hemorrhage. Emerging data suggest distinct profiles, with internal adenomyosis more closely related to implantation failure, recurrent pregnancy loss, and placental complications, whereas external adenomyosis is more frequently associated with endometriosis and primary infertility. However, phenotype-specific associations require further validation. Accurate phenotypic characterization may improve reproductive counseling and individualized management. Prospective studies using standardized diagnostic criteria are needed to confirm phenotype-specific risks and develop targeted therapeutic and obstetric strategies.